2007
DOI: 10.1007/s11214-007-9204-4
|View full text |Cite
|
Sign up to set email alerts
|

The Solar Electron and Proton Telescope for the STEREO Mission

Abstract: The Solar Electron and Proton Telescope (SEPT), one of four instruments of the Solar Energetic Particle (SEP) suite for the IMPACT investigation, is designed to provide the three-dimensional distribution of energetic electrons and protons with good energy and time resolution. This knowledge is essential for characterizing the dynamic behaviour of CME associated and solar flare associated events. SEPT consists of two dual double-ended magnet/foil particle telescopes which cleanly separate and measure electrons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 16 publications
2
95
0
1
Order By: Relevance
“…Since our main focus is on the acceleration efficiency for electrons, we have analyzed the electron data critically with respect to a potential proton contamination. This effect is described in detail in the paper by Müller-Mellin et al (2008a) and is shown in Fig. 15 of that paper using GEANT 4 simulations.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Since our main focus is on the acceleration efficiency for electrons, we have analyzed the electron data critically with respect to a potential proton contamination. This effect is described in detail in the paper by Müller-Mellin et al (2008a) and is shown in Fig. 15 of that paper using GEANT 4 simulations.…”
Section: Introductionmentioning
confidence: 86%
“…The second unit is mounted in the north/south direction. The work by Müller-Mellin et al (2008a) clearly shows that protons with energies between 450 and 650 keV contaminate the SEPT electron channels. The same simulations show that, above 400 keV, electrons may also contribute to the ion channels.…”
Section: Instrumentationmentioning
confidence: 99%
“…The electron observations used in this work are provided by the Solar Electron and Proton Telescope (SEPT, Müller-Mellin et al 2008) onboard the STEREO spacecraft and the Electron Proton and Alpha Monitor (EPAM) onboard ACE (Gold et al 1998). The SEPT instrument measures electrons in the range of 45-400 keV.…”
Section: Instrumentationmentioning
confidence: 99%
“…8.3 are associated with SEP events observed at 1 AU from the Sun, by instruments at L1 or by the twin STEREO spacecraft, or both. Proton and/or electron enhancements are observed with SoHO/ERNE (Torsti et al 1995), STEREO/LET (Mewaldt et al 2008), STEREO/HET (von Rosenvinge et al 2008), STEREO/SEPT (Müller-Mellin et al 2008), and ACE/EPAM (Gold et al 1998) over a wide range of energy (55 keV to 4 MeV for electrons and 1.6 to 130 MeV for protons). Higher energy protons are available from SoHO/EPHIN (penetrating protons at 100-1000 MeV energies) as well as from GOES/HEPAD (only for 9 of the 25 investigated Fermi/LAT events, see Fig.…”
Section: Solar Energetic Particle Events Associated With Fermi/lat Gamentioning
confidence: 99%